2011
DOI: 10.1386/eta.7.3.245_1
|View full text |Cite
|
Sign up to set email alerts
|

Cultural dialogues in European art education: Strategies for enhancing children’s culture and constructing diversity

Abstract: The aim of our article is to discuss the potential of art education to enhance children’s culture. In so doing, we are contributing to a debate that began at the InSEA congress in Rovaniemi (2010) during the symposium on cultural diversity. The article is based on recent research and art pedagogy projects conducted by the writers in five European countries: Finland, Italy, Portugal, Spain and Sweden. When comparing and evaluating these projects, we focus on the space given to children’s culture and on the pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In other words, the community supported the individual to grow his potential, and the individual could contribute his ideas to the community (Dewey, 1927;Koivula & Hännikäinen, 2017). Prior research concurs with our findings that children's joint activity and collective thinking can produce new, shared cultural knowledge (Koivula & Hännikäinen, 2017;Mercer, 2013;Rusanen et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In other words, the community supported the individual to grow his potential, and the individual could contribute his ideas to the community (Dewey, 1927;Koivula & Hännikäinen, 2017). Prior research concurs with our findings that children's joint activity and collective thinking can produce new, shared cultural knowledge (Koivula & Hännikäinen, 2017;Mercer, 2013;Rusanen et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Imagining positive encounters with another cultural group has shown to increase children's positive attitudes towards that group (Miles & Crisp, 2014). Other studies have shown that creating works of art together can promote encountering between two cultural groups, because the creative process opens up opportunities to negotiate shared realities (Askins & Pain, 2011;Einarsdottir et al 2009;Rusanen et al, 2011;Siim, 2020). What is important is that the children or young people have the freedom to lead the creative process, as adult-led projects may block the children from engaging in shared negotiation (Askins & Pain, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier research, I described methods to promote the development of visual knowledge-building and learning through visual and multimodal tools. These studies describe children's activities in different creative projects, both within and outside of preschool and primary school that give children access to learning environments and monitor meaningful activities through the use of art as a cultural tool (Rusanen et al, 2011). Through communicative and participatory forms, children take part in cultural activities and visual art education in early childhood and primary school educational settings (Häikiö, 2007;Karlsson Häikiö, 2012, 2017bKarlsson Häikiö & Ericson, 2017).…”
Section: Introductionmentioning
confidence: 99%